2016
DOI: 10.18632/oncotarget.10729
|View full text |Cite
|
Sign up to set email alerts
|

Ago-RIP-Seq identifies Polycomb repressive complex I member CBX7 as a major target of miR-375 in prostate cancer progression

Abstract: Prostate cancer is a heterogeneous disease. MiR-375 is a marker for prostate cancer progression, but its cellular function is not characterized. Here, we provide the first comprehensive investigation of miR-375 in prostate cancer. We show that miR-375 is enriched in prostate cancer compared to normal cells. Furthermore, miR-375 enhanced proliferation, migration and invasion in vitro and induced tumor growth and reduced survival in vivo showing that miR-375 has oncogenic properties in prostate cancer. On the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Each of the miRNAs identified for inclusion in the panel has previously been associated with carcinogenesis, though not all have been associated with prostate carcinogenesis. MiR-375 is well-described in the carcinogenesis and progression pathways of prostate cancer (22,23) as well as pancreatic ductal adenocarcinomas (24) and has been proposed as both a diagnostic (25) and a prognostic (26) biomarker for prostate cancer. Increased expression of miR-375 has been found in prostate cancer cells, as compared to normal cells (22,23), indicating a pro-oncogenic role despite it's anti-invasive and anti-epithelial-mesenchymal transition properties (27).…”
Section: Discussionmentioning
confidence: 99%
“…Each of the miRNAs identified for inclusion in the panel has previously been associated with carcinogenesis, though not all have been associated with prostate carcinogenesis. MiR-375 is well-described in the carcinogenesis and progression pathways of prostate cancer (22,23) as well as pancreatic ductal adenocarcinomas (24) and has been proposed as both a diagnostic (25) and a prognostic (26) biomarker for prostate cancer. Increased expression of miR-375 has been found in prostate cancer cells, as compared to normal cells (22,23), indicating a pro-oncogenic role despite it's anti-invasive and anti-epithelial-mesenchymal transition properties (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests that miR‐375 is involved in the epithelial‐mesenchymal‐transition (EMT) signature, and that disruption of this regulatory network may result in altered expression of miR‐375. Another recent report suggests miR‐375 mediated repression of the tumor suppressor CBX7, a member of the Polycomb complex involved in epigenetic regulation, which may be associated with prostate tumorigenesis …”
Section: Discussionmentioning
confidence: 99%
“…For example, Hannon et al used AGO2 antibody to capture RISC and isolated bound mRNAs for further analysis with microarray, followed by identifying targets for miR-124 [32]. Similarly, target genes in RISC were isolated with AGO antibody and further analyzed by RNA-seq for identifying targets for miR-375 and miR-155 [33,34]. Using antibodies targeting GW182 family proteins AIN-1 and AIN-2, Han et al isolated and identified miRNA targets in RISC of C. elegans [35].…”
Section: Immunoprecipitationmentioning
confidence: 99%